Causes of Acute Intranatal and Postnatal Hypoxia in Neonatal Infants - S. A. Perepelitsa; A. M. Golubev; V. V. Moroz; S. V. Alekseyeva (Общая реаниматология)
Objective: to study the causes of acute intranatal hypoxia and reveal a relationship of placental changes to respiratory failure (RF) in newborn infants. Subjects and methods. The investigation included 252 neonates with the complicated course of an early neonatal period. Their gestational age was 26 weeks to 40 weeks, birth weight varied from 850 g to 4100 g. 95.3% of the newborn infants were born with a low Apgar score and RF, which required mechanical ventilation immediately after birth. The neonatal status was clinically evaluated; the values of blood gas composition and acid-base balance were recorded; the pathogen was discharged from the tracheobronchial tree; chest X-ray survey and placental morphological examination were performed. Results. The main cause of neonatal respiratory failure is chronic intrauterine hypoxia caused by placental inflammatory changes and fetal-placental blood circulatory disorders, which gives rise to preterm delivery, cerebral hemodynamic disorders, and neonatal amniotic fluid aspiration. Bacteriological examination of tracheobronchial aspirations showed that no microflora growth occured in the majority of the newborns acute intranatal hypoxia. Enterococcus faecalis and Staphylococcus epidermidis were isolated in 12.3% and 8.7%, respectively. Growth of в-hemolytic streptococcus was observed in 2.8% of cases. The rate of microbial association specific only for rate premature infants with neonatal respiratory distress syndrome (NRDS) was 4.8%. Conclusion. Placental changes causing fetal-placental circulatory disorders were ascertained to be responsible for acute intranatal and postnatal neonatal hypoxia. Placental inflammatory changes occurred in the majority of cases, as confirmed by bacteriological examinations of neonatal infants. Isolation of the varying microbial flora in infants with RF to a greater extent is, indicative of the infectious process occurring in the maternal body. Key words: acute intranatal hypoxia, neonatal amniotic fluid aspiration, intrauterine infection.